Implementasi Teknik Enkoding Digital Pembacaan Sensor Ultrasonik Untuk Memetakan Keputusan Aksi Robot Quadruped - Oggy Setiawan; Dahnial Syauqy; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Technology development has created various kinds of technology improvement, especially in robotics. Legged-robots has several advantages; they can move in both smooth and rough areas, wavy, uneven or flat, climb the stairs, avoid and step in the distractions. One of the problem in designing a robot's ability is the robot's localization system to know the position in a certain time. Digital encoding technique is a series of combination that produces specific output such as binary as a response to one or more active input that is used to simplify data and can be built from a simple logic gate AND and OR. The digital encoding process start from the making of truth table, digital encoding technique formula, and simplification by K-MAP. Implementing digital encoding technique using 8 ultrasonic sensors to map 8 motor actions of the quadruped robot. Testing is done in three things; the accuracy of ultrasonic sensor HC-SR04, digital encoding computing time, and the accuracy of classification result in digital encoding technique. From the test we can get robot's motor action accuracy by implementing digital encoding technique as much as 98% with the average computing time is around 0,15 seconds when one of the sensors is given a 7 cm incline and 0,17 seconds when one of the sensors is given a 20 cm incline.